2021
DOI: 10.1002/ange.202016185
|View full text |Cite
|
Sign up to set email alerts
|

Doubling the Stakes: The Promise of Halide Double Perovskites

Abstract: When the stakes are doubled in a wager, a player must correctly place two consecutive bets to win, but the payout is larger. Similarly, two B sites in combination dictate the properties of A2BB′X6 (A=monocation, X=halide) double perovskites. Correctly picking two B sites is more challenging than picking just one, as in the AIBIIX3 single perovskites, but the options are greater and, we believe, the rewards are higher when the stakes are doubled. In this Minireview, we emphasize fundamental aspects of halide do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 187 publications
0
5
0
Order By: Relevance
“…The double perovskite structure allows incorporation of diversified range of cations into the octahedrally coordinated B/B’ site. [ 9 ] This open a plethora of electronic and compositional structure tuning that can lead to varying fundamental properties geared toward determining a potential substitute to MAPbI 3 as a solar absorber.…”
Section: Introductionmentioning
confidence: 99%
“…The double perovskite structure allows incorporation of diversified range of cations into the octahedrally coordinated B/B’ site. [ 9 ] This open a plethora of electronic and compositional structure tuning that can lead to varying fundamental properties geared toward determining a potential substitute to MAPbI 3 as a solar absorber.…”
Section: Introductionmentioning
confidence: 99%
“…This approach also provides more choices for the B-site cations. 17 Recently, the vacancy-ordered double perovskite A 2 BX 6 has attracted great attention due to its high stability and nontoxicity, and the research has been carried out in a variety of tetravalent cation compounds. Tang et al 18 systematically studied the geometric structures and electronic and optical Te elements are of the same main group, studies have also shown that substituting the A-site cations can improve perovskite solar cells' stability and photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The effective strategy to remove lead is to replace two divalent lead ions with a monovalent cation and a trivalent cation or a tetravalent cation and a vacancy to form double perovskites with the chemical formula of A 2 B + B 3+ X 6 or A 2 B 4+ X 6 , , where A represents monovalent cations such as Cs + and Rb + , the B + , B 3+ , and B 4+ represent monovalent cations, trivalent cations, and tetravalent cations, respectively, and X represents halogen ions such as Cl – , Br – , and I – . This approach also provides more choices for the B-site cations . Recently, the vacancy-ordered double perovskite A 2 BX 6 has attracted great attention due to its high stability and nontoxicity, and the research has been carried out in a variety of tetravalent cation compounds.…”
Section: Introductionmentioning
confidence: 99%
“…2 In halide double perovskites, monovalent metals M I (Cu, Ag, Au, Na and K) and trivalent ones M III (In, Sb, Bi, Tl, Au, Y and Gd) are octahedrally coordinated and orderly arranged in structure, resulting in extended compositional diversity and rich electronic structure relative to “single” lead halide perovskites. 3 Tetravalent metals and vacancies can also be used to replace Pb, forming K 2 PtCl 6 -type structures which can also be classified as the halide double perovskites. 4…”
mentioning
confidence: 99%
“…2 In halide double perovskites, monovalent metals M I (Cu, Ag, Au, Na and K) and trivalent ones M III (In, Sb, Bi, Tl, Au, Y and Gd) are octahedrally coordinated and orderly arranged in structure, resulting in extended compositional diversity and rich electronic structure relative to ''single'' lead halide perovskites. 3 Tetravalent metals and vacancies can also be used to replace Pb, forming K 2 PtCl 6type structures which can also be classified as the halide double perovskites. 4 Since the potential photovoltaic application of Cs 2 AgBiX 6 (X = Cl and Br) was described in 2016, 5 many three-dimensional (3D) halide double perovskites have been synthesized and their optoelectronic properties were fully characterized.…”
mentioning
confidence: 99%